Cloning, Sequencing and Characterization of The Xylan Degrading Enzymes from Geobacillus thermoleovorans IT-08 - Ni Nyoman Tri Puspaningsih; Antonius Suwanto; Maggy T Suhartono (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2008)
Geobacillus thermoleovorans IT-08 is a Gram positive, thermophilic bacterium that can utilize xylan as a sole source of carbon. This strain was isolated from Gunung Pancar hot spring, Bogor, West Java, Indonesia. A plasmid genomic library in Escherichia coli DH5α was constructed and screened for xylanase activity. One positive clone, namely DH5α (pTP510) has been isolated, sequenced and showed putative exo-xylanase (exo-xyl), β-xylosidase (xyl), and α-L-arabinofuranosidase (abfa) genes (Genebank Accession No.DQ387047, DQ345777 and DQ387046 respectively). Each gene encoded 604, 511 and 502 amino acids, respectively. The BLAST search for protein database revealed that Abfa was high similar with GH51 family Abfa of Geobacillus stearothermophilus T6, but Xyl and Exo-Xyl were slight similar with GH43 family (25-34%) respectively. The deduced protein had a molecular weight of about 70 kDa (Exo-Xyl), and 60 kDa (Xyl and Abfa). These showed good accordance with the calculated molecular weight of each protein (68.64 kDa for Exo-xyl, 57.99 kDa for Xyl and 57.03 kDa for Abfa) from deduced amino acid sequence.